EHF is a novel regulator of cellular redox metabolism and predicts patient prognosis in HNSCC. Issue 2 (27th May 2022) - Oyelakin, Akinsola; Nayak, Kasturi Bala; Glathar, Alexandra Ruth; Gluck, Christian; Wrynn, Theresa; Tugores, Antonio; Romano, Rose-Anne; Sinha, Satrajit
Abstract: Head and Neck Squamous Cell Carcinoma (HNSCC) is a heterogeneous disease with relatively high morbidity and mortality rates. The lack of effective therapies, high recurrence rates and drug resistance driven in part, by tumor heterogeneity, contribute to the poor prognosis for patients diagnosed with this cancer. This problem is further exacerbated by the fact that key regulatory factors contributing to the disease diversity remains largely elusive. Here, we have identified EHF as an important member of the ETS family of transcription factors that is highly expressed in normal oral tissues, but lost during HNSCC progression. Interestingly, HNSCC tumors and cell lines exhibited a dichotomy of high and low EHF expression, and patients whose tumors retained EHF expression showed significantly better prognosis, suggesting a potential tumor suppressive role for EHF. To address this, we have performed gain and loss of function studies and leveraged bulk and single-cell cancer genomic datasets to identify global EHF targets by RNA-sequencing (RNA-seq) and Chromatin Immunoprecipitation and next generation sequencing (ChIP-seq) experiments of HNSCC cell lines. These mechanistic studies have revealed that EHF, acts as a regulator of a broad spectrum of metabolic processes, specifically targeting regulators of redox homeostasis such as NRF2 and SOX2. Our immunostaining results confirm the mutually exclusive expression patterns of EHF and SOX2 in HNSCC tumors and suggest a possible role for these two factors in establishing discrete metabolic states within the tumor microenvironment. Taken together, EHF may serve as a novel prognostic marker for classifying HNSCC patients for actionable and targeted therapeutic intervention. Graphical Abstract: